AN INTENSIFIED PRAGMATISM IN REPSONSE TO REPRODUCTIVE EXPERIENCES AND MEDICALIZATION: A CASE STUDY OF CAPE BRETON WOMEN - Graham, Elizabeth (My University, 2003)
This dissertation focuses on the reproductive experiences of Cape Breton women. Using feminism and symbolic interactionism, I explore these experiences by conducting focus group and semi-structured individual interviews with 47 women from the Cape Breton Regional Municipality. Three major themes emerged from the women's stories. First, women assess their situations and make decisions to maximize their advantages. Second is what I characterize as women's "intensified" pragmatism engendered by their complex socio-cultural environment. Problems of high unemployment, severe pollution and difficult access to health care have contributed to a culture that encourages individuals to expect the worst and to trust only those closest to them. In relation to women's reproductive experiences, this translates into distrust of medical professionals, great reliance on other women, and culturally influenced understandings of normal reproductive processes. Third, the advantages women identify for using medical interventions and treatments are subjective, arising out of lived experiences. For those not privy to the women's experiences or those operating from a biomedical position, these advantages may seem counter-productive or paradoxical. Considering the three themes as related parts of a whole, I found the difficulties and disadvantages associated with life in Cape Breton resulted in a strengthening of women's agency. Given the constraints on access to health care and the social problems, these women had no choice but to improvise and be pragmatic. Theoretically, this research reaffirms the need to pull together the literature focusing on structural constraints and lay perspectives to understand the role of medicalization in women's lives. It also illustrates that control is an important issue not just in women's interactions with medical professionals, but also in interactions between women. Substantively, this work contributes to our understanding of women's pragmatism, the importance of the context in which it operates, and how these impact on women's definitions of normal reproductive experiences.
Keywords: Sociology; Sociology